Emotional factors are critical motivators for tobacco use according to smokers’ own perception - Sarafim-Silva, Bruna Amélia Moreira [UNESP]; Valente, Vitor Bonetti [UNESP]; Duarte, Gabrielle Dias [UNESP]; Nishida, Clícia Keiko Sakamoto; Fani, Edilze Fatima Gardenal; Miyahara, Glauco Issamu [UNESP]; Biasoli, Éder Ricardo [UNESP]; Bernabé, Daniel Galera [UNESP] (Springer Nature, 2019)
Aim: Psychological factors play an important role in tobacco dependence. However, few investigations have focused on smokers’ own perception about motivations for tobacco consumption using open-ended questions. Subject and method: In this study, we used the Collective Subject Discourse (CSD) method to investigate the motivations for tobacco use according to smokers’ own perception in 135 current smokers. Results: The vast majority of patients (83.7%) reported that they smoked cigarettes when seeking relief or emotional comfort. When asked why they smoked, most declared they smoked due to stress, anxiety, or nervousness. Long-term smokers reporting using cigarettes to feel pleasure, in contrast to short-term smokers, who mostly reported they smoked because they felt stress or anxiety (p < 0.001). Most of the patients (71.2%) also reported emotional factors as the reason for increasing the desire to smoke. Heavy smokers smoked more in moments when they felt alone compared to light smokers (p = 0.034). Conclusion: The smokers’ collective discourses demonstrate that from their own perception, psychological factors are the motivational basis for their use of cigarettes. Therefore, most smokers are conscious of the impact of emotional factors on smoking dependence, and this may play a critical role in quit-smoking programs, as well as presenting an important factor for public health.
Keywords: Addiction behaviour; Emotional disorder; Psychological factors; Smoking; Tobacco use